Shaking Table Tests on Wrap Rope Connect Device for Continuous-Beam Bridges with Different Pier Heights - Yanfang Liu; Wenxue Zhang; Xiuli Du; Weigang Bao (Advances in Civil Engineering)
To investigate the cooperative and isolation effectiveness of the wrapped rope connect device (WRCD) on continuous-beam bridges with different pier heights, shaking table tests were conducted on a typical three-span continuous-beam bridge model. The model had additional pier stiffness and applied the WRCD. Two actual seismic waves with different spectral characteristics and multiple intensities were used for input ground motion. By examining the performance and measured structural response under various excitations, WRCD could effectively improve the overall cooperative effect of the model structure for a limited increase in the input seismic energy of the system. The acceleration ratio from the fixed pier top to the movable pier top increased from∼17% without the WRCD to∼32% with it. The strain-response ratio of the pier bottom decreased from its maximum of 24.8 times to 3.6 times after the device was applied. There is a specific relationship between the influence and the pier height of the structure, and the rules for high and low piers slightly differ. The movable and fixed ports can be coordinated by setting reasonable design parameters of the WRCD, which can be used for the seismic design of continuous-beam bridges with different pier heights.